Optimal control of an induction heating Process for thixoforming - Masserey, A.; Rappaz, J.; Rozsnyo, R.; Touzani, R. (IEEE transactions on magnetics, 2004)
We investigate in this paper a numerical method to control the temperature of an induction heating process through electric current parameters such as frequency and current voltage imposed to the terminals of the inductor. We consider in this paper an optimal control problem arising in an induction heating process. The control parameters are here the frequency and the voltage supply. More precisely, We seek a sinusoidal voltage function whose amplitude varies in time. For this, we use a two-dimensional induction heating model that involves a phase transition in which the magnetic field has only one nonvanishing component. The procedure can be extended to more sophisticated models without major modification of the optimal control problem. We present a numerical control algorithm and discuss numerical experiments that prove the efficiency of the procedure.